Additive-Driven Sinterability Improvement of Mullite Ceramics for Co-firing with Cu-Mo - Lim, Chang-Bin; Yeo, Dong-Hun; Shin, Hyo-Soon (Asian Journal of Chemistry, 2013)
The needs for electrodes and materials to realize a low resistance are increasing as the line widths of a circuit are reduced for an increase in the number of layers due to increasingly higher integration of semiconductor wafers as well as impedance matching of transmission lines. Consequently, Cu-Mo electrodes have been considered for application to realize a lower resistance than that of the existing Mo electrodes used with mullite materials. When mullite ceramics and Cu-Mo electrode were simultaneously fired, resistivity was not reduced because of interaction between the electrode and the ceramic at 1400 ºC, while resistivity decreased below 1370 ºC. It was verified that sintering should be conducted at a temperature as low as 1350 ºC to realize a low resistance by applying Cu-Mo electrodes to the mullite ceramics. When sintering was conducted at 1350 ºC with addition of 1 wt % of SiO2, 1 wt % of MgO, 1.5 wt % of Y2O3 and 7 wt % of SrCO3 to mullite, an excellent sinterability was exhibited at a density of 3.22 g/cm3.